2010
DOI: 10.1007/s10900-010-9342-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Viral Hepatitis Among Puerto Rican Adults: Implications for Prevention

Abstract: Although primary prevention of HAV and HBV can be achieved through vaccination, the burden of HCV can only be reduced through behavioral interventions to reduce its risk factors. This study evaluated knowledge regarding transmission, clinical manifestations and prevention of viral hepatitis in Puerto Rico. We assessed the level of knowledge about HAV (six questions), HBV (12 questions) and HCV (eight questions) among non-institutionalized Puerto Rican adults aged 21–64 years. Demographic characteristics and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
(39 reference statements)
5
21
2
Order By: Relevance
“…This proportion is consistent with the findings reported by other studies with Asian populations (47.5-69%) [24,27] and is lower than the results of a recent study in Puerto Rico (74.4%) [30]. Less than 10% of the respondents correctly indicated that HBV is more easily spread than HIV, which is also lower than the range of 19-27% reported in other studies [24,30]. A mere 36% of study subjects correctly reported that a HBV vaccine exists, which is substantially lower than the finding of 52.5% reported by Soto-Salgado et al [30].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This proportion is consistent with the findings reported by other studies with Asian populations (47.5-69%) [24,27] and is lower than the results of a recent study in Puerto Rico (74.4%) [30]. Less than 10% of the respondents correctly indicated that HBV is more easily spread than HIV, which is also lower than the range of 19-27% reported in other studies [24,30]. A mere 36% of study subjects correctly reported that a HBV vaccine exists, which is substantially lower than the finding of 52.5% reported by Soto-Salgado et al [30].…”
Section: Discussionsupporting
confidence: 92%
“…Only 53% of the participants responded correctly that HBV and HCV can be spread during sexual intercourse with an infected person. This proportion is consistent with the findings reported by other studies with Asian populations (47.5-69%) [24,27] and is lower than the results of a recent study in Puerto Rico (74.4%) [30]. Less than 10% of the respondents correctly indicated that HBV is more easily spread than HIV, which is also lower than the range of 19-27% reported in other studies [24,30].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations